2003
DOI: 10.1071/sr02114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyacrylamide additions on infiltration and erosion of disturbed lands

Abstract: The removal of vegetation and disturbance of the soil surface due to a range of human activities results in the potential for soil structure degradation and sediment movement. Polyacrylamides have been used to improve infiltration and reduce erosion on agricultural lands. However, they are not commonly used as part of management and rehabilitation programs on land disturbed by construction or mining activities in Australia. A study was undertaken to investigate the potential for polyacrylamides to improve infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Clay polymer interactions are of primary importance in numerous scientific fields ranging from materials science, where numerous studies are devoted to the synthesis and characterization of clay nanocomposites (e.g., [1,2]), to soil science and agronomy, where clay polymer interactions in soils control to a large extent soil structure and plant nutrition (e.g., [3][4][5]). Clay polymer interactions are also particularly important in the numerous applications in which clay flocculation processes play a role, for instance, in mineral processing, oil drilling, paper making, or water clarification.…”
Section: Introductionmentioning
confidence: 99%
“…Clay polymer interactions are of primary importance in numerous scientific fields ranging from materials science, where numerous studies are devoted to the synthesis and characterization of clay nanocomposites (e.g., [1,2]), to soil science and agronomy, where clay polymer interactions in soils control to a large extent soil structure and plant nutrition (e.g., [3][4][5]). Clay polymer interactions are also particularly important in the numerous applications in which clay flocculation processes play a role, for instance, in mineral processing, oil drilling, paper making, or water clarification.…”
Section: Introductionmentioning
confidence: 99%
“…Their results were somewhat similar to an earlier study with anionic PAMs (Levy and Agassi, 1995) using similar application rates sprinkled at 48 mm 11-. In rainfall simulator studies on mine soils, Vacher et al (2003) saw improved erosion control with higher molecular weight formulations, but no differences in infiltration. PAM performance in their study was enhanced on soils with higher clay contents.…”
Section: Pam Properties Affecting Efficacymentioning
confidence: 99%
“…They can also pose significant challenges to revegetation because of poor infiltration and, when rainfall is seasonal, due to sheet erosion of seeded areas before stand establishment has had a chance to occur. Vacher et al (2003) studied the use of PAM in large erosion plots using soil from three Australian mine sites. A range of PAM materials and application rates and strategies were studied in replicated tests under a rainfall simulator.…”
Section: Pam For Construction Sites and Other Disturbed Landsmentioning
confidence: 99%
“…During the last two decades, PAM has become widely accepted for soil erosion control in intensive agriculture with furrow irrigation as well as on steep road embankments (Agassi and Ben-Hur, 1992;Lentz et al, 2002;Ben-Hur, 2006;Sojka et al, 2007). Since PAM is a generic term for a broad class of hundreds of polymers with differing functional groups and chain lengths, different formulations have been tested to achieve optimal binding of PAM with the soils' specific clay particles, through direct ionic attractions or cation bridges (Vacher et al, 2003). So far, few field trials have assessed the effectiveness of PAM in recently burnt areas, and these studies have reported opposing results.…”
Section: Mitigation Of Soil Erosion Following Wildfiresmentioning
confidence: 99%